Performance of one-view breast tomosynthesis as a stand-alone breast cancer screening modality: results from the Malmö Breast Tomosynthesis Screening Trial, a population-based study - Lång, Kristina (Eur Radiol, 2015)
OBJECTIVE: To assess the performance of one-view digital breast tomosynthesis (DBT) in breast cancer screening. METHODS: The Malmö Breast Tomosynthesis Screening Trial is a prospective population-based one-arm study with a planned inclusion of 15000 participants; a random sample of women aged 40–74 years eligible for the screening programme. This is an explorative analysis of the first half of the study population (n = 7500). Participants underwent one-view DBT and two-view digital mammography (DM), with independent double reading and scoring. Primary outcome measures were detection rate, recall rate and positive predictive value (PPV). McNemar's test with 95 % confidence intervals was used. RESULTS: Breast cancer was found in sixty-eight women. Of these, 46 cases were detected by both modalities, 21 by DBT alone and one by DM alone. The detection rate for one-view DBT was 8.9/1000 screens (95 % CI 6.9 to 11.3) and 6.3/1000 screens (4.6 to 8.3) for two-view DM (p < 0.0001). The recall rate after arbitration was 3.8 % (3.3 to 4.2) for DBT and 2.6 % (2.3 to 3.0) for DM (p < 0.0001). The PPV was 24 % for both DBT and DM. CONCLUSION: Our results suggest that one-view DBT might be feasible as a stand-alone screening modality. KEY POINTS: • One-view DBT as a stand-alone breast cancer screening modality has not been investigated. • One-view DBT increased the cancer detection rate significantly. • The recall rate increased significantly but was still low. • Breast cancer screening with one-view DBT as a stand-alone modality seems feasible.